CFD Simulation And Validation Of The In-Cylinder Within A Motored Two Stroke Si Engine - M. M., Noor; K., Kadirgama; D., Ramasamy; M. S. M., Sani (2008)

(untitled)
The study of in-cylinder characteristic is important to understand the scavenging process of the two-stroke engine. It is important to design a new two-stroke engine to produce low emission that will meet current and future emission regulation. The objective of the paper is to evaluate and analyze a Computational Fluid Dynamic (CFD) simulation of the flow in motored loop scavenged two-stroke engine using commercial software FLUENT and compare with experimental data. The experiment is carried out using the motored method which the rotating engine is generated using motor and without firing. The data is collected at different engine speed from the engine idle speed to maximum engine speed. After the validation, there are relative error between the experiment method and simulation method that need to be observed.